Folklore as an Invaluable Source of Information and a Fertile Object of Humanitarian Studies - Сердега, Руслан Леонідович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
Folklore is an invaluable source of information about a particular nation, its history, culture, aesthetic tastes and preferences, behavioral patterns, moral norms and values. It is also a means of transmission of this information between generations. In this article we demonstrate the significance of folklore for various branches of the Humanities, social life etc. We note that the folklore itself and the language of folklore is a fertile subject for many academic and scientific sectors and disciplines.